Variation of 16SrRNA gene for Some Nosocomial Bacteria Isolated from Ramadi Teaching Hospital for Women and Children - Saade Abdalkareem Jasim1 , Sumaya Ayad abdulrazzaq1 , Saba ‚a Muhsen Farhan1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of this studsy is to diagnose bacterial strains in hospitals by the 16SrRNA gene and to know thevariation of the nucleotide sequence. The study of bacteria in hospitals is of great importance to identify theextent of change in these species and their resistance to antibiotics. This indicates that these bacteria have theability to change or obtain new variants to be able to resist antibiotics. In this study, samples were taken fromdifferent locations of the Ramadi Teaching hospital for women and children and were cultured on differentmedia. They were also stained and examined under light microscopy and some biochemical tests wereconducted. Pure colonies were obtained after re-culture and then extracted the DNA from the 16 isolatedsamples and measuring its concentration. Using the specific primer for 16SrRNA genes, the samples wereamplified by a PCR and the size was shown to be 1500 bp. The unknown bacteria were sent to the sequence.Some samples showed variations in comparison with the data presented by NCBI. This is evidence of somevariations shown by bacteria to overcome antibiotics and increase their severity and spread in hospitals,whether in kitchens, emergency or preterm infants, as well as laboratory staff and lab equipment.